Perceptions and Knowledge Around Substance Use Disorders and the Role of Occupational Therapy: A Survey of Clinicians - Amy M Mattila; Gabriella Santacecilia; Rebecca LaCroix (SAGE Publishing, 2022)
Background: Today's healthcare system requires practitioners to acquire a level of confidence, knowledge, and personal desire that enables them to treat a growing clientele with substance use disorders (SUDs). Although SUDs impact millions of Americans, there are many barriers to receiving treatment. It is important to understand how occupational therapy (OT) practitioners' perceptions of working with clients who experience SUDs relate to the knowledge and skills required to identify and provide treatment. Method: Two surveys, the Medical Regard Scale and modified Drug Problems Perceptions Scale, were utilized to analyze participants attitudes, perceptions, and knowledge around working with individuals with SUDs. Data was collected from 116 practitioners with a variety of experience, practice settings, and backgrounds in understanding SUDs. Results: The majority of respondents reported no formal training in treating clients with SUDs (72.4%). In terms of attitudes around working with this population, a fraction reported a preference not to work with patients experiencing SUDs (16.0%) or finding them "irritating" to work with (12.9%), while 62.0% reported they felt especially compassionate toward this population. The majority of respondents felt that insurance plans should cover patients like this to the same degree that they cover patients with other conditions; however, only 48.3% had a clear idea of their responsibilities in helping individuals with SUDs. In regard to knowledge around working with SUDs, just over half of respondents reported a true working knowledge of SUDs and SUDs related problems (53.4%). Conclusion: Occupational therapy practitioners would benefit from additional training, resources, and support related to provision of services to individuals with SUD. In addition, training to continue to reduce stigma within the profession can potentially increase access to care.